PEMANFAATAN PERPUSTAKAAN GUNA MENINGKATKAN MINAT BACA MAHASISWA PENDIDIKAN GURU SEKOLAH DASAR FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS MUHAMMADIYAH PROF. DR. HAMKA - Sri Agustina; Nani Solihati; Ika Yatri (Prosiding Seminar Nasional Berseri, 2020)
This research is motivated by the low reading interest of Indonesian society which is getting worse, especially in formal institutions, namely universities which are educational institutions that are deliberately presented to provide the generation of the nation in order to develop their potential to continue the lives of society and the future. The goal is to find out the use of libraries to increase reading interest in elementary school teacher education students at the Faculty of Teacher Training and Education at the Muhammadiyah University Prof. DR. HAMKA. This type of research method is qualitative descriptive which has the nature of telling and interpreting existing data about a process that is taking place. In this study carried out with a cross sectional approach that is ex post facto because this study did not observe or carried out continuously over a long period of time, but in a relatively short time. Data analysis is done deductively, and the validity of the data is done by data triangulation. Based on the results of the study, it is known that the use of libraries to increase reading interest in Elementary School Teacher Education students of the Faculty of Teacher Training and Education at the University of Muhammadiyah Prof. DR. HAMKA which can be seen from the aspects of facilities and infrastructure as well as facilities both at the UHAMKA FKIP library and the lab library. FKIP UHAMKA PGSD.